2024
DOI: 10.1038/s41598-023-50442-4
|View full text |Cite
|
Sign up to set email alerts
|

Apply EZStrobe to simulate the finishing work for reducing construction process waste

Pham Vu Hong Son,
Pham Van Tien

Abstract: Vietnam, classified as a developing nation, encounters numerous challenges within its construction sector, including the scarcity of comprehensive and documented historical data regarding risks and a deficiency in embracing contemporary methodologies to mitigate the impact of risk factors on construction project objectives. This paper outlines initial findings from an ongoing research endeavor that centers on implementing Lean Construction (LC) techniques to enhance construction management practices specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…While earlier strategies were considered to be more focused on resource efficiency improvements, LC focuses on flow efficiency improvements [9]. It has been demonstrated that by identifying waste sources and applying LC principles such as "just-in-time", "multi-skilled teams", etc., the cycle time of a construction project was reduced by 13%, technical efficiency was improved by 141%, average productivity increased by 268%, and labor costs were reduced by 96% [10].…”
Section: Introductionmentioning
confidence: 99%
“…While earlier strategies were considered to be more focused on resource efficiency improvements, LC focuses on flow efficiency improvements [9]. It has been demonstrated that by identifying waste sources and applying LC principles such as "just-in-time", "multi-skilled teams", etc., the cycle time of a construction project was reduced by 13%, technical efficiency was improved by 141%, average productivity increased by 268%, and labor costs were reduced by 96% [10].…”
Section: Introductionmentioning
confidence: 99%